2017
DOI: 10.1177/0956797616677313
|View full text |Cite|
|
Sign up to set email alerts
|

Can a Word Sound Like a Shape Before You Have Seen It? Sound-Shape Mapping Prior to Conscious Awareness

Abstract: Nonarbitrary mappings between sound and shape (i.e., the bouba-kiki effect) have been shown across different cultures and early in development; however, the level of processing at which this effect arises remains unclear. Here we show that the mapping occurs prior to conscious awareness of the visual stimuli. Under continuous flash suppression, congruent stimuli (e.g., "kiki" inside an angular shape) broke through to conscious awareness faster than incongruent stimuli. This was true even when we trained people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 34 publications
1
49
1
1
Order By: Relevance
“…These effects are known to be automatic (Parise & Spence, 2012), unconscious (Hung, Styles & Hsieh, 2017), and to enhance memory for individual word meanings under certain conditions (Imai, Haryu & Okada, 2005; Kantartzis, Imai & Kita, 2011; Lockwood, Dingemanse & Hagoort, 2016). The finding of differential effects at different level of labelling draws an interesting parallel with existing research into category learning in the absence of sound symbolism.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are known to be automatic (Parise & Spence, 2012), unconscious (Hung, Styles & Hsieh, 2017), and to enhance memory for individual word meanings under certain conditions (Imai, Haryu & Okada, 2005; Kantartzis, Imai & Kita, 2011; Lockwood, Dingemanse & Hagoort, 2016). The finding of differential effects at different level of labelling draws an interesting parallel with existing research into category learning in the absence of sound symbolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that sound symbolic effects emerge in a culture without a writing system (Bremner et al, 2013), in preliterate infants (Ozturk et al, 2013;Peña et al, 2011;cf. Fort et al, 2013;Pejovic & Molnar, 2016), with learned neutral orthographies (Hung et al, 2017), and are not affected by direct manipulations of font (Sidhu, Pexman, & Saint-Aubin, 2016), it seems probable that orthography is, as the very least, not the sole contributor to these effects. Nevertheless the contribution of orthography relative to those of acoustics and articulation is still an open question.…”
Section: Outstanding Issues and Future Directionsmentioning
confidence: 99%
“…Rendall, 2011). They may also emerge on implicit tasks, such that congruent phoneme-stimuli pairings are responded to differently than incongruent pairings (e.g., Hung, Styles, & Hsieh, 2017;Ohtake & Haryu, 2013;Westbury, 2005).…”
mentioning
confidence: 99%
“…Recently, the fundamental nature of the bouba-kiki effect has been further explored by Hung, Styles, and Hsieh (2017), who claimed that sound-shape mappings affect cognitive processing even before people become aware of the stimuli. Relying on a technique called continuous flash suppression (henceforth CFS; Tsuchiya & Koch, 2005), Hung and colleagues found that congruent combinations of shapes and words (i.e., kiki presented in an angular shape or bubu presented in a round shape) gained preferential access to awareness over incongruent combinations (i.e., kiki in a round shape or bubu in an angular shape).…”
mentioning
confidence: 99%
“…In light of the debate in the literature on what kind of information can be extracted from words and non-words under CFS, Hung et al's (2017) finding is intriguing. For instance, Yang and Yeh (2011) found that neutral words broke suppression faster than negative words, but Sklar et al (2012) reported the opposite for two-word combinations (e.g., black eye versus sand box).…”
mentioning
confidence: 99%